The Temperature Anisotropy and Helium Abundance Features of Alfvénic Slow Solar Wind Observed by Parker Solar Probe, Helios, and Wind Missions - Jia Huang; Davin E. Larson; Tamar Ervin; Mingzhe Liu; Oscar Ortiz; Mihailo M. Martinović; Zhenguang Huang; Alexandros Chasapis; Xiangning Chu; B. L. Alterman; Zesen Huang; Wenwen Wei; et al. (The Astrophysical Journal Letters)
Slow solar wind is typically characterized as having low Alfvénicity, but the occasional occurrence of highly Alfvénic slow solar wind (HASSW) raises questions about its source regions and evolution. In this work, we conduct a statistical analysis of temperature anisotropy and helium abundance in HASSW using data from the Parker Solar Probe (PSP) within 0.25 au, Helios between 0.3 au and 1 au, and Wind near 1 au. Our findings reveal that HASSW is prevalent close to the Sun, with PSP observations displaying a distinct “U-shaped” Alfvénicity distribution with respect to increasing solar wind speed, unlike the monotonic increase trend seen in Helios and Wind data. This highlights a previously unreported population of unusually low-speed HASSW, which is found in both sub-Alfvénic and super-Alfvénic regimes. The observed decreasing overlap in temperature anisotropy between HASSW and fast solar wind (FSW) with increasing heliocentric distance suggests different underlying heating processes. Additionally, HASSW exhibits two distinct helium abundance populations, particularly evident in PSP data, with generally higher helium abundance compared to less Alfvénic slow solar wind. Moreover, the decreasing overlap in temperature anisotropy versus helium abundance distributions between HASSW and FSW with decreasing radial distance implies that not all HASSW originates from the same source region as FSW.